E-concussion? an investigation of the representation of head impact events and concussion within popular sport-based video games - Freja J. Petrie; Nathan Howarth; Samantha C. Bureau; Chris J. Nowinski; James S. Woodward; Isaac Lockett (PLoS ONE, 2025)
Guidelines have been produced to support the management of concussion, an injury commonly experienced in amateur and elite sports. To improve adherence to concussion guidelines, there is a need to improve their dissemination to the public. Mass media is inherently well positioned to distribute this information; however, concussion must be framed accurately and appropriately to avoid the spread of misinformation. To date the extent to which concussion is depicted in video games is unknown, despite their widespread audience and evidenced use as educational tools. Therefore, this study investigated the representation of concussion (and head impact events) in four sport-based video games. Matches from EA Sports FC 24 (EA Sports, n = 16), EA Sports FC 25 (EA Sports, n = 16), Rugby League Live 4 (Tru Blu, n = 18) and Rugby 22 (Nacon and Bigben Interactive S.A, n = 18) were simulated via a Playstation 5 (Sony Interactive Entertainments). Frequency of direct head impact events and references to concussion were reported. Head impact events were observed in all games (EA Sports FC 24 n = 253, EA Sports FC 25 n = 331, Rugby League Live 4 n = 93, Rugby 22 n = 215). A single concussion was reported in Rugby League Live 4 via a dialogue box. No references to medical intervention or concussion protocols were made in any games analysed. The lack of reference to concussion protocols is a missed opportunity to exemplify appropriate concussion behaviours.